Eddington [videorecording (Blu-Ray)] - Aster, Ari; Phoenix, Joaquin; Pascal, Pedro; Grimes, Luke, 1984-; O'Connell, Deirdre (Actress); Ward, Micheal, 1995-; Hoeferle, Amélie; Collins, Clifton, Jr; Belleau, William, 1982-; Butler, Austin, 1991-; Stone, Emma, 1988-; Khondji, Darius; et al. (A24, 2025)
"In May of 2020, a standoff between a small-town sheriff and mayor sparks a powder keg as neighbor is pitted against neighbor in Eddington, New Mexico."--